Analisis Kepuasan Kerja Karyawan Pada PT XYZ - Keyla Larasati; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This research uses a qualitative descriptive approach, namely by analyzing and describing the problems found. This research is based on primary data and secondary data. Primary data in this research was obtained using data collection techniques in the form of observation, interviews and documentation. Secondary data was obtained from books, previous research, and articles related to research related to employee job satisfaction. Researchers also used a data collection method in the form of a survey sent to 20 employees. The purpose of this research is to determine employee job satisfaction at PT. XYZ from various departments and also knows the factors that trigger job satisfaction for employees at PT. XYZ. The results of this research show that the majority of employees express a fairly high level of job satisfaction with their work, but there are still some employees who do not feel job satisfaction with their work or work environment. This research provides insight for company management which can enable the company to identify ways that can be implemented in an effort to increase employee job satisfaction at PT. XYZ. Thus, there will be an increase in overall company performance.